Does fish stocking rate affect the photosynthesis of Lactuca sativa grown in an aquaponic system? - Zuzanna Malwina Jaszczuk; Adam Brysiewicz; Agnieszka Kozioł; Alicja Auriga; Marian Brestic; Hazem M. Kalaji (Journal of Water and Land Development, 2023)
The depletion of natural resources such as freshwater and cropland makes it necessary to find a new solution for sustainable food production. Aquaponic systems seem to be a great alternative to traditional agriculture, however, there are still many unknowns that need to be explored. It is already known how fish stocking affects water quality in aquaponic systems, but not how it affects the plants’ growth, and especially on chlorophyll fluorescence. In this study, we examined how the density of 0, 2, 4, 8, and 16 stocking fish in five aquaria affects lettuce growth. The first tank was only a hydroponic system with plants but without fish (control). In the remaining four aquaria – 2, 4, 8 and 12 specimens of common carp fry with an average weight of 20 grams (average 8.5–33.2 g) were placed in the aquaponic growing system. Physicochemical analysis of water was conducted to determine the levels of pH, electrical conductivity ( EC), N-NO 3, N-NO 2, N-NH 4, P-PO 4, O 2 and physiological parameters of plants (nitrogen balance index – NBI, chlorophyll content index – CCI, quantum yield – QY, flavonoid content – Flv) were analysed. The results showed that fish stocking density has different effects on plant physiological parameters, but in most cases, was insignificant. It seems that the greater number of fishes and higher density indirectly causes growth inhibition (lower photosynthetic efficiency) due to the increase of N-NO 3 and a decrease of O 2 in the water.